Prosocial Behaviours of Members from Student Voluntary Clubs in Sagaing University of Education - Yar Zar Chit (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
This study investigated the prosocial behaviors of members from student voluntary clubs in Sagaing University of Education, Myanmar. A total of 200 BEd students who are members from six student voluntary clubs in Sagaing University of Education participated in this study. Descriptive research design and survey method were used.  Findings revealed that mean percentage of emotional prosocial behavior is highest and that of anonymous prosocial behaviour is lowest. There were significant differences in students’ altruistic and emotional prosocial behaviors as well as there was significant difference in their prosocial behaviors by gender at  =0.05 levels. However, there was no significant difference in students’ prosocial behaviours by club type.  It was also found that there were commonly positive high correlations between total prosocial behavior and each tendency at  =0.05 levels. This study hopes to give some ideas to promote students’ prosocial behaviours.